THE INSTITUTIONAL STATUS OF THE CENTRAL BANK AS THE BASIS FOR EFFECTIVE MONETARY REGULATION - DZIUBLIUK, Oleksandr (Scientific journal «World of Finance», 2026)
Вступ. У статті досліджено інституційний статус центрального банку як ключового фактора ефективного монетарного регулювання та підтримання макрофінансової стабільності в умовах ринкової економіки. Показано, що еволюція центральних банків від емісійних центрів до повноцінних органів монетарної влади зумовила необхідність чіткого визначення їхнього місця в системі державного управління.Мета – проаналізувати інституційний статус центрального банку як головний чинник ефективності монетарного регулювання в умовах сучасних економічних викликів.Результати. Встановлено, що інституційний статус центрального банку формується через поєднання правового, структурного, функціонального, персонального та фінансового вимірів. Визначено, що правовий статус закріплює пріоритет стабільності грошової одиниці, структурний вимір – місце центрального банку як верхнього рівня дворівневої банківської системи, а функціональний, персональний і фінансовий виміри забезпечують операційну незалежність. Доведено, що саме узгодженість цих складових забезпечує автономність центрального банку, його здатність реалізовувати монетарну політику та протидіяти політичному тиску. Визначено, що інституційний статус центрального банку є основою його суверенної ролі в економіці та реалізується через чотири фундаментальні функції. Проаналізовано особливості статусу Національного банку України на законодавчому рівні та відзначено головні суперечності, що виникають у процесі реалізації монетарної політики.Висновки. Сформований належним чином інституційний статус центрального банку є фундаментом стабільності грошової одиниці й ефективного державного впливу на економічні процеси через монетарне регулювання, оскільки забезпечує автономію в ухваленні рішень, запобігаючи неконтрольованій емісії та фінансуванню бюджетного дефіциту. Однак подальше удосконалення інституційної спроможності центрального банку у монетарній сфері потребує оптимізації законодавства і розвитку фінансового ринку.Introduction. The article examines the institutional status of the central bank as a key foundation for effective monetary regulation and maintaining macro-financial stability in a market economy. It is shown that the evolution of central banks from emission centers to full-fledged monetary authorities has necessitated a clear definition of their place in the system of public administration.The purpose of this article is to analyze the institutional status of the central bank as a key factor in the effectiveness of monetary regulation in the context of contemporary economic challenges.Results. It has been established that the institutional status of a central bank is formed through a combination of legal, structural, functional, personal, and financial dimensions. It is determined that the legal status establishes the priority of the stability of the monetary unit, the structural dimension is the place of the central bank as the top level of the two-tier banking system, and the functional, personal and financial dimensions ensure operational independence. It has been proven that it is the consistency of these components that ensures the autonomy of the central bank, its ability to implement monetary policy and counteract political pressure. It is determined that the institutional status of the central bank is the basis of its sovereign role in the economy and is implemented through four fundamental functions. The features of the status of the National Bank of Ukraine at the legislative level are analyzed and the main contradictions that arise in the process of implementing monetary policy are noted.Conclusions. A properly formed institutional status of the central bank is the foundation of the stability of the monetary unit and effective state influence on economic processes through monetary regulation, as it ensures autonomy in decision-making, preventing uncontrolled money issuance and financing of the budget deficit. However, further development of the central bank's institutional capacity in the monetary sphere requires not only legislative improvement, but also financial market development.